2012
DOI: 10.1371/journal.pone.0034142
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Catalytically Impaired Taspase1T234V or Taspase1D233A Variants Does Not Have a Dominant Negative Effect in T(4;11) Leukemia Cells

Abstract: BackgroundThe chromosomal translocation t(4;11)(q21;q23) is associated with high-risk acute lymphoblastic leukemia of infants. The resulting AF4•MLL oncoprotein becomes activated by Taspase1 hydrolysis and is considered to promote oncogenic transcriptional activation. Hence, Taspase1’s proteolytic activity is a critical step in AF4•MLL pathophysiology. The Taspase1 proenzyme is autoproteolytically processed in its subunits and is assumed to assemble into an αββα-heterodimer, the active protease. Therefore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 33 publications
(109 reference statements)
0
15
0
3
Order By: Relevance
“…To experimentally demonstrate that the presumed nucleophile is indeed required for dTaspase1's proteolytic activity, Thr 195 was mutated into Val, in analogy to the catalytically inactive human Taspase1 T134V mutant (10, 13). To investigate protease function in living cells, we first tested whether our translocation biosensor assay could be adapted to Drosophila cells (8, 13) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To experimentally demonstrate that the presumed nucleophile is indeed required for dTaspase1's proteolytic activity, Thr 195 was mutated into Val, in analogy to the catalytically inactive human Taspase1 T134V mutant (10, 13). To investigate protease function in living cells, we first tested whether our translocation biosensor assay could be adapted to Drosophila cells (8, 13) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, hydrophobicity in combination with size is required for productive cleavage. Whereas in both enzymes, position P2′ is highly flexible, specific residues at positions P3′ and P4′ seem to be only required for human Taspase1 (10, 12), explaining why the human Taspase1 degradome is much more restricted. In contrast to previous predictions (9, 22), the identified cleavage motif for dTaspase1 strongly implies an enlarged degradome containing 70 potential substrates in Drosophila in contrast to the rather limited 27 targets predicted for humans (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleophile Thr 234 is generated by autoproteolysis (cis cleavage) of the proenzyme in 2 subunits, α28 and β22, which assemble to form the active protease. Whereas crystal structures of threonine aspartase 1 and other type 2 asparaginases suggest the formation of an asymmetric abba‐heterotetramer (17), in vivo studies revealed that threonine aspartase 1 is already active as αβ‐monomer (18, 19). The essential role of the catalytically active nucleophile Thr 234 for the functionality of threonine aspartase 1 is significant.…”
Section: Structure and Function Of Threonine Aspartasementioning
confidence: 99%
“…6). As the threonine aspartase 1 proenzyme is autoproteolytically cleaved and assumed to assemble into a heterodimer, overexpression of inactive threonine aspartase 1 mutants would inhibit the formation of active protease dimers (genetic inhibition) (18). However, recent in vivo studies demonstrated that endogenous threonine aspartase 1 predominantly exists as an ab‐monomer, and over‐expression of inactive mutants has no effect on its proteolytic activity (18).…”
Section: Threonine Aspartase 1 Is a Disease‐relevant Protease And Potmentioning
confidence: 99%